MiR-19a-3p Suppresses M1 Macrophage Polarization by Inhibiting STAT1/IRF1 Pathway - Xiaoxiao Zhu; Xiaoxiao Zhu; Xiaoxiao Zhu; Qiang Guo; Qiang Guo; Qiang Guo; Jing Zou; Bin Wang; Zhen Zhang; Zhen Zhang; Zhen Zhang; Ran Wei; et al. (Frontiers Media S.A., 2021)
Macrophages, an important type of immune cells, are generally polarized to classically activated macrophage (M1) or alternatively activated macrophage (M2) to respond to environmental stimuli. Signal transducer and activator of transcription 1 (STAT1), a very important transcription factor, can promote M1 macrophage polarization. However, the mechanisms of regulating STAT1 in macrophage polarization remain unclear. In the present study, STAT1 was markedly elevated, however, miR-19a-3p was down-regulated in interferon (IFN)-γ and lipopolysaccharide (LPS) treated RAW264.7 cells, and dual-luciferase reporter assay identified that miR-19a-3p directly targeted STAT1 by binding to its 3'UTR. Up-regulated miR-19a-3p inhibited M1 polarization by targeting STAT1/interferon regulatory factor 1 (IRF1) and vice versa in vitro. Consistently, overexpression of miR-19a-3p in LPS treated mice by systemically administering agomiR-19a-3p effectively reduced the inflammation in mouse lung tissues, and inhibited M1 macrophage polarization via suppressing STAT1/IRF1 pathway. In summary, our study confirmed that miR-19a-3p, as a direct regulator of STAT1, inhibited M1 macrophages polarization. The miR-19a-3p/STAT1/IRF1 pathway can potentially be used to design novel immunotherapy for modulating macrophage polarization.